A case for mandatory ultrasound training for rural general practitioners: a commentary - Annie Arnold; Richard Fleet; David Lim (James Cook University, 2021)
Context: Point-of-care ultrasound is a rapidly evolving technology that enables rapid diagnostic imaging to be performed at a patient's bedside, reducing time to diagnosis and minimising the need for patient transfers. This has significant applications for rural emergency and general practice, and could potentially prevent unnecessary transfers of patients from rural communities to more urban centres for the purpose of diagnostic imaging, reducing costs and preventing disruption to patients' lives. Meta-analyses on point-of-care ultrasound have reported extremely high sensitivity and specificity when detecting lung pathology, and the potential applications of the technology are substantial. A significant application of the technology is in the care of rural paediatric patients, where acute lower respiratory pathology is the most common cause of preventable deaths, hospitalisations, and emergency medical retrievals from remote communities for children under five. Issues: Although widely available, point-of-care ultrasound technology is not widely utilised in Australian emergency departments and general practices. Issues with comprehensive training, maintenance of skills, upskilling and quality assurance programs prevent physicians from feeling confident when utilising the technology. In Canada, point-of-care ultrasound training is part of the core competency training in the Royal College of Physicians of Canada emergency medicine fellowship program. Point-of-care ultrasound is widely used in rural practice, although lack of training, funding, maintenance of skills and quality assurance were still listed as barriers to use. Lessons learned: Point-of-care ultrasound is a highly sensitive and specific technology with wide potential applications. Issues with quality control and maintenance of skills are preventing widespread use. Coupling point-of-care ultrasound with telemedicine could help increase the usability and accessibility of the technology by reducing the issues associated with maintenance of skills and quality assurance.